Right ventricular structure and function as possible determinants of surgical outcome 30 years after repair of tetralogy of Fallot - Mesquita,Sonia F. (2003)
OBJECTIVE: To identify the variables that may be involved in the persistence of symptoms (functional class II, III, or IV vs. I) in patients being followed up for 30 years after surgical repair of tetralogy of Fallot. METHODS: Fifty-three patients (27 women), who underwent corrective surgery for tetralogy of Fallot between 1960 and 1970, were studied. Their ages ranged from 7 months to 26 years. At the end of follow-up, 13 patients were asymptomatic and the remaining were in functional class II (N=24), III (N=15), and IV (N=1). To differentiate asymptomatic from symptomatic patients, the following variables were analyzed: age at surgery, need for widening the pulmonary ring and trunk, need for a second (2nd OP) or 3rd operation, residual defect of the interventricular septum, residual regurgitation of the pulmonary valve, systolic gradient through the right ventricular outflow tract, right ventricular dilation or hypertrophy (RVH), cardiothoracic index (CTI), right and left ventricular ejection fraction (RVEF/LVEF), and arrhythmias. RESULTS: The univariate analysis showed an association between the presence of symptoms and the 2nd OP (P=0.03), an increase in the CTI (P=0.0001), moderate to severe RVH (P=0.002), and dilation (P=0.0003). In the logistic regression model, the combination of the 2nd OP (P=0.008), the RVH (P=0.002), and the reduction in RVEF (P=0.01) determined the presence of symptoms. CONCLUSION: Despite the surgical treatment, right ventricular remodeling and performance were the major determinants in the late follow-up of tetralogy of Fallot.